TOTAL OCCLUSION IN THE LEFT SUBCLAVIAN ARTERY LEADING TO SUBCLAVIAN STEAL SYNDROME IN A MIDDLE AGED MAN - Gilbert Tangkudung; Marcelle Yulianne (Jurnal Sinaps, 2021)
Background: Subclavian steal syndrome is the manifestation of subclavian steal phenomenon. Clinical manifestations include vertebra-basilar signs such as vertigo, dizziness, ataxia, dysarthria, and syncope. Recurrent weakness on the left hand is also a common manifestation. Treatment includes conservative approach for mild case. Invasive treatments includes stenting and angioplasty are reserved for highly symptomatic case. Case: Male, 48 years old, presented with recurrent TIA in a form of weakness of left extremities preceded spinning sensation occurred five times a day. Blood pressure examination on right and left arm showed a difference of 20mmHg in systolic blood pressure. Patient had a history of hypertension and was also a smoker. Head MRI examination revealed multiple infarctions. Cerebral angiography revealed a total occlusion of left subclavian artery indicated a subclavian steal phenomenon. Patient was treated with pharmacological therapy and lifestyle modifications. These approach resulted in improvement of the symptoms.Conclusion: Subclavian steal syndrome is a rare case. It is important to consider this diagnosis on patient with recurrent vertebro-basilar manifestations or TIA. Severity of symptoms determines treatment approach.